Desempenho de semeadora-adubadora em função do prepa ro de solo e espa çamento da cultura do milho - Chioderoli, Carlos Alessandro [UNESP]; Furlani, Carlos Eduardo Angeli [UNESP]; Da Silva, Rouverson Pereira [UNESP]; De Castilho Gitti, Douglas [UNESP]; Kaneko, Flávio Hiroshi [UNESP]; Roman, Rodrigo Alberto Alândia [UNESP] (My University, 2010)
The performance of machines and agricultural implements are of fundamental importance, especially when subjected to different types of soil tillage, and have to adapt to these conditions, in order to promote good operational performance. The objective of this study was to analyze the operational performance of a Marchesan Supreme Cop grain drill, equipped with four rows, spaced 0.90 m, according to three types of tillage: conventional tillage (plowing and two harrowing series), reduced tillage (scarification with a roller), and no-tillage, in areas previously seeded with maize (Zea mays L.), at two spacing measures (0.90 m and 0.45 m). The results indicate that the demand for power, tensile stress, and motor rotation, in the sowing operation, were not influenced by tillage and maize crop. The tractor wheel slip showed different results, being lower in no-tillage and higher in conventional and reduced tillage.
Performance of a grain drill in function of soil tillage and MAIZE crop spa cing
Keywords: Agricultural machinery; Operational capacity; Sowing; Wheel slip; Zea mays L.; Zea mays